Seroprevalence of human immunodeficiency virus among antenatal patients and incidence of mother- to- child transmission using single dose nevirapine: a cohort study in Maharashtra - Bhuyar, Sonal A.; Kale, Pratibha V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective was to study the seroprevalence of human immunodeficiency virus (HIV) in antenatal patients and to find out the incidence of mother to child transmission (MTCT) using single dose nevirapine (sdNVP) to mother- baby pairs in labour. Methods: This prospective study was conducted in the department of Obstetrics & Gynecology, Dr. PDMMC, Amravati, Maharashtra from February 2010 to May 2015. All pregnant women attending the antenatal clinic were subjected to pretest counseling and HIV testing after informed consent. The HIV +ve pregnant patients who opted for delivery at our hospital were included in the study. sdNVP was administered to mother- baby pairs according to NACO guidelines. Babies of these patients were followed up to 18 months of age for HIV testing. Results: 12077 antenatal patients underwent pretest counseling. 11957 antenatal patients were tested for HIV of which 28 were detected positive. Therefore, the seroprevalence in this study was found to be 0.23%. 23 patients delivered at our hospital during the study period and babies of 2 patients tested positive for HIV. Hence the incidence of MTCT was found to be 9.5% in our study. Conclusions: Universal screening of pregnant patients for HIV and judicious use of PPTCT regimens can significantly reduce MTCT of HIV and prevalence of pediatric HIV infection. Single dose nevirapine use over last few years has successfully reduced MTCT, but our aim should be to reduce it further with more effective ART regimens for the seropositive antenatal patients and their babies.